PENERAPAN MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA WATTPAD DALAM PEMBELAJARAN MENGIDENTIFIKASI UNSUR DRAMA DI KELAS VIII SMPN 2 DAYEUHKOLOT - Alifia Nurfitriani; Eggie Nugraha; Meity Suratiningasih (STKIP Subang, 2023)
This research was conducted because of the low ability of students in reading drama texts and the difficulties they experienced when analyzing elements of drama. Factors causing this include the lack of use of creative and innovative learning models and media by educators. The purpose of this study was to describe the ability of students in learning to identify elements of drama using the Problem Based Learning model assisted by Wattpad media and to compare the differences in the abilities of students in the control class and the experimental class in learning to identify drama elements using the Problem Based Learning model assisted by Wattpad media. The method used in this study was a quasi-experimental method with pre-test and post-test designs as well as a control group. The results showed that students' abilities increased in learning to identify elements of drama using the Problem Based Learning model assisted by Wattpad media. There was an increase in the pretest average score from 63.39 to 88.54 in the experimental class posttest. There is a significant difference between the learning outcomes of students in the experimental class and the control class, with the average posttest score of the experimental class being 88.54 while the control class is 84.59